A Simulation Study On The Effects of Cutting Fluid in Drilling Process - AZMAN, MUHAMMAD AMAR IMRAN; IBRAHIM, RASIDI (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Nowadays, manufacturing is the transformation of a starting material's geometry, properties, and appearance for the production of components or products using technical physical and chemical processes. This is because it is crucial to maintain the quality of the cutting tool product. In this project, the workpiece material is Carbon Steel S45C type and the material on drill bits is Carbon Steel. This project uses two methods to investigate the effect of drill bit temperature: dry drilling and drilling with cutting fluids. DEFORM 3D has been utilized for the drilling process in the current in the current study. The 3D drill bit was designed using SOLIDWORKS software with STL file and then executed in simulation software. When the point angle is 135° and the feed rate is 0.10mm/rev, the highest dry drilling temperature is 428°C. When the point angle is 135° and the feed rate is 0.125mm/rev, the highest drilling temperature is 317°C for a drill using cutting fluid. When the point angle is 135°, the highest stress effective value is 1980mm/rev for dry drilling, and 1860mm/rev for drilling with cutting fluid when the point angle is 130°. The value of drill bit temperature increased with the increasing value of feed rate and the value of stress effective is increased when the value of the point angle of the drill bit is increase.